SISTEM PENGELOLAAN HARTA WAKAF DI KANTOR KEMENTERIAN AGAMA KOTA BANDA ACEH - Muzakkir Zabir (Sekolah Tinggi Ilmu Syariah (STIS) Al-Aziziyah Sabang, 2022)
The issue of waqf is a problem that must be handled properly in Aceh, considering that Aceh with its Qanun has set very detailed provisions regarding the issue of waqf, therefore in Banda Aceh which is the capital of the province and also an area that was very impacted by the 2004 Tsunami, a system is needed that very good for managing it, what's more, the treasures of the Tsunami are very much found in the city of Banda Aceh. To make this research more focused, the authors chose a field research approach (Qualitative Research). The results show that it is very difficult to manage waqf assets because there are no more heirs who have bequeathed their land, for various reasons, considering the Tsunami that hit Aceh on December 24, 2004, so many heirs have died, resulting in the property there is no certificate yet, even though land certificates or shops that have been inherited need to be made so that there is no such thing as being sold and so on. With events like this, in the end the purpose of waqf is not achieved optimally. There is also a coaching system for nazirs at the Office of the Ministry of Religion of Banda Aceh City, which is carried out by the Ministry of Religion of Banda Aceh City, and not all nazirs participate in this coaching, but it is carried out in three stages then all nazirs in Banda Aceh City can be fostered, given the very low budget. and depending on DIPA funds and the process also takes a long time, this is a bit of a delay in developing nazir in Banda Aceh City. The challenge faced by the Office of the Ministry of Religion of the City of Banda Aceh in managing waqf assets, which is the most difficult for the Ministry of Religion of the City of Banda Aceh, is the placement of people who use waqf land without realizing that the land is not theirs and what is even worse is that it is sold, all of which are documents to sue no longer exists, this is a big challenge that must be solved by the Ministry of Religion of Banda Aceh City. Keywords: System, Management, Waqf Assets